A generalized short-term unit commitment methodology for analyzing electric power and natural gas integrated systems - Tovar Ramírez, Cecile Alejandra (Universidad Michoacana de San Nicolás de Hidalgo, 2019)
The increasing global use of natural gas for electric power generation has led to a greater interdependence between natural gas and electric infrastructures which, in turn, presents new challenges for power and gas system operators to achieve an operation reliable and efficient daily routine of both systems. This thesis proposes a generalized approach to assigning units in the short term to optimize the hourly assignment of thermal generation considering the interdependence between the natural gas and electricity infrastructures. This generalized approach is formulated as a mixed-integer nonlinear optimization problem where an optimal model of gas and multi-period alternating current power flows is incorporated to the problem of assigning thermal units. Contrary to all the other proposals that ignore the dispatch of reactive power and the restrictions of the alternating current electrical network, as well as restrictions associated with primary regulation to solve the problem of allocation of units considered by the integrated electricity and natural gas system, the proposed solution approach simultaneously co-optimizes the allocation and dispatch of active and reactive power, while taking into account the set of physical and operational constraints associated with each infrastructure. This set of constraints includes limits on reactive power generation, magnitude of nodal voltages, frequency deviation, and gas flow dynamics constraints. The solution is obtained by decomposing this generalized optimization problem into two mutually connected optimization subproblems: one spatially separable related to the unit assignment problem and the other temporarily separable associated with the unified co-optimization of both energy systems, which are solved sequentially. until the same dispatch of hourly generation in both subproblems is obtained.

El creciente uso global del gas natural para la generación de energía eléctrica ha dado lugar a una mayor interdependencia entre las infraestructuras de gas natural y eléctrica que, a su vez, presenta nuevos desafíos para los operadores de sistemas de potencia y gas para lograr una operación diaria confiable y eficiente de ambos sistemas. Esta tesis propone un enfoque generalizado de asignación de unidades a corto plazo para optimizar la asignación horaria de generación térmica considerando la interdependencia existente entre las infraestructuras de gas natural y de electricidad. Este enfoque generalizado está formulado como un problema de optimización no lineal entero-mixto donde es incorporado un modelo óptimo de gas y de flujos de potencia de corriente alterna multi-período al problema de asignación de unidades térmico. Contrario de todas las demás propuestas que ignoran el despacho de potencia reactiva y las restricciones de la red eléctrica de corriente alterna, así como restricciones asociadas con regulación primaria para resolver el problema de asignación de unidades que considera el sistema integrado de electricidad y gas natural, el enfoque de solución propuesto co-optimiza simultáneamente la asignación y el despacho de potencia activa y reactiva, mientras toma en cuenta el conjunto de restricciones físicas y operativas asociadas con cada infraestructura. Este conjunto de restricciones incluye límites de generación de potencia reactiva, de magnitud de voltajes nodales, de desviación de frecuencia y restricciones de la dinámica del flujo de gas. La solución se obtiene al descomponer este problema de optimización generalizado en dos subproblemas de optimización mutuamente conectados: uno espacialmente separable relacionado con el problema de asignación de unidades y el otro temporalmente separable asociado con la cooptimización unificada de ambos sistemas de energía, que se resuelven secuencialmente hasta que el mismo despacho de generación horario en ambos subproblemas es obtenido.
Facultad de Ingeniería Eléctrica. Doctorado en Ciencias en Ingeniería Eléctrica
Keywords: info:eu-repo/classification/cti/7; FIE-D-2019-1629; Programación no lineal entera-mixta; Asignación de unidades con restricciones de seguridad; Reserva primaria; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3376